Determinan Kualitas Audit - Sri Ayem; Lilis Alviana Yakob (Universitas Batanghari, 2022)
The purpose of this study was to determine the effect of Auditor Experience (X1), Objectivity (X2), Independence (X3, and Accountability (X4) on audit quality at the Yogyakarta Public Accounting Firm. This type of research is quantitative research. The population in this study is all auditors. who works at a Public Accounting Firm located in the Special Region of Yogyakarta. The sampling method used purposive sampling. Data was collected through questionnaires and obtained 7 KAPs located in Yogyakarta with a sample of 40 respondents. Then the data was processed using SPSS IBM Version 25, technique The data analysis used is descriptive statistical test, classical assumption test, multiple regression test, t test, f test, and determinant coefficient (RÂ²).The results of this study are to prove the auditor experience variable has a positive effect on audit quality, objectivity variable has no effect on quality. audit, independent variables have an effect h is positive on audit quality and the accountability variable has a positive effect on audit quality